2018
DOI: 10.29252/ijrm.16.5.315
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin protect sperm, seminiferous epithelium and pituitary-gonadal axis from torsion-detorsion injury: An experimental study

Abstract: Background:Troxerutin is a flavonoid antioxidant that protect different organ against damage caused by ischemia-reperfusion.Objective:The aim of this study was to evaluate the effect of troxerutin in reducing the damages caused by ischemia-reperfusion in rat's testis.Materials and Methods: 40 Male Wistar rats (2 month old) were divide to four groups (n=10). Group1 (sham), Group 2 (control, ischemia-reperfusion (I/R) without treatment), Group 3 (I/R+150 mg/kg of troxerutin), and group 4 (I/R+20 mg/kg of vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
(56 reference statements)
2
2
0
Order By: Relevance
“…Another study has shown that TRX is capable of reversing mastocytosis [18]. According to Kheirollahi et al [53], flavonoids reverse tissue damage by preventing neutrophil and mast cell degranulation, which corroborates with the findings obtained in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Another study has shown that TRX is capable of reversing mastocytosis [18]. According to Kheirollahi et al [53], flavonoids reverse tissue damage by preventing neutrophil and mast cell degranulation, which corroborates with the findings obtained in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Serum testosterone levels in the torsion/detorsion groups were found to be significantly decreased when compared to the control group. The decrease in testosterone has been similarly reported in previous testicular ischemia studies (Abdelzaher et al, 2020;Shakoohi et al, 2018;Kheirollahi et al, 2018). The decrease in testosterone may be associated with damage to the Leydig cells (Benny et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, studies using experimental models for the treatment of testicular torsion are still being conducted. Many protective agents have been researched over the years (Bodur et al., 2016; Kheirollahi et al., 2018; Semercioz et al., 2017). However, despite all the research conducted, a treatment method with easy clinical adaptation and proven benefits has yet to be discovered.…”
Section: Introductionmentioning
confidence: 99%